The application of fullerene black as nanomodifier for cast iron - Ускенбаева, А.М.; Шамельханова, Н.А. (Recent Contributions to Physics, 2016)
In the article is considered the possibility of nanostructured carbon in the form of fullerene black (FB ) as nano-additive to modifier for cast iron. In context of scarce materials and energy saving, given application FB that contains fullerene-like structures is actual task. The possibility of nano-modification of cast iron with FB-additives is substantiated by their reactivity, taking into account modern ideas about fullerene nature of cast iron. Active carbon nanostructures containing in the melt of cast iron, which is modified with FB-nanoadditives, determines modifying effect. Modification is connected with increase of graphitization degree, elimination of cementite phase and increase of tribological properties of the casting. Given model of nucleation of graphite inclusions under the influence of FB-modifier reflects the mechanism of nano modifying of cast iron.Theoretical study of interaction mechanism of nanostructured carbon in the FB and nanoscale elements presenting in molten iron cast (according to Davidov S.V.) is based on the research of crystallization process of metal melts.